Financial intermediation in a global environment - Victoria Nuguer (Banco de México, 2015)
I develop a two-country DSGE model with global banks (financial intermediaries in one country lend to banks in the other country). Banks are financially constrained on how much they can borrow from households. The main goal is to obtain a framework that captures the international transmission of a financial crisis through the balance sheet of the global banks, as well as to explain the insurance mechanism of the international asset market. A negative shock to the value of the capital in one country generates a global financial crisis through the international interbank market. In this model, unconventional credit policies help to mitigate the effects of a financial disruption. The policies are carried out by the policy maker of the country directly hit by the shock. Consumers of that country are better off with policy than without it, while consumers from the other country are worse off.
Keywords: G01; E44; F40; G21; 330; global financial crisis; global banking; asset prices; financial frictions